2018
DOI: 10.1002/fam.2500
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relationship between the particle size distribution and the effectiveness of the K‐powder fire extinguishing agent

Abstract: Summary The relationship between the particle size distribution and the extinguishing effectiveness of the new K‐powder fire extinguishing agent has been studied experimentally, to explore the reason of the great extinguishing efficiency exhibited by the new K‐powder fire extinguishing agent on Class B fire (liquid fuel fire). The results of the experiment showed that the extinguishing effectiveness increased along with the decrease of the particle size distribution. In addition, a sharp discontinuity appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The flame‐inhibition ability of Ca(OAc) 2 was the highest flame‐inhibition ability among the tested calcium compounds, as summarized in Table 2; however, the CaO powder generated from Ca(OAc) 2 had the largest D 32 value among the samples, as listed in Table 3. Several researchers 33–36 have discovered a negative relation between particle size and fire‐suppression ability; the fact contradicts the findings of particle size analyses. Consequently, we rejected hypothesis (i) and we concluded that Ca(OAc) 2 's extinguishing ability is most likely governed by a factor (ii): its high ability to generate inert gases.…”
Section: Plausible Fire‐suppression Mechanismsmentioning
confidence: 93%
“…The flame‐inhibition ability of Ca(OAc) 2 was the highest flame‐inhibition ability among the tested calcium compounds, as summarized in Table 2; however, the CaO powder generated from Ca(OAc) 2 had the largest D 32 value among the samples, as listed in Table 3. Several researchers 33–36 have discovered a negative relation between particle size and fire‐suppression ability; the fact contradicts the findings of particle size analyses. Consequently, we rejected hypothesis (i) and we concluded that Ca(OAc) 2 's extinguishing ability is most likely governed by a factor (ii): its high ability to generate inert gases.…”
Section: Plausible Fire‐suppression Mechanismsmentioning
confidence: 93%
“…However, halon extinguishing agent is harmful to the environment and has been banned for a long time [2][3][4]. In recent years, many scholars have studied a large number of extinguishing agents [5][6][7][8][9][10][11] that can replace halon. After comprehensively considering the spraying cost and extinguishing effect, ultrafine dry powder is considered as the extinguishing agent for the WTFT.…”
Section: Introductionmentioning
confidence: 99%
“…The search for alternatives promoted the examination of the effectiveness of several gasses, liquids, and dry powder agents 3–6 . It was shown that the dry powder agents that contain the elements Na and K were the most effective in extinguishing fires, especially NaHCO 3 (SB) and KHCO3 (PB), which have been widely used and proved to be several times more effective than Halon 1301 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] It was shown that the dry powder agents that contain the elements Na and K were the most effective in extinguishing fires, especially NaHCO 3 (SB) and KHCO3 (PB), which have been widely used and proved to be several times more effective than Halon 1301. [7][8][9] In designing dry powder agents, particle diameter and base were important factors. First, there is a significant correlation between particle diameter and the flame-inhibiting effectiveness of dry powder agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation